2001
DOI: 10.1111/j.1477-9552.2001.tb00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Co‐operatives: An Incomplete Contracting Perspective

Abstract: M arkcting co-operatives (MCs) are analysed from an incompbte contracting perspective. The requirement of the domination of control by the members of an MC is a threat to the survival of an MC in markets where the level of asset specificity at the processing stage of production is increasing. Howcw~ an MC may remnin an efficient governance stnicture when the increasing h e 1 of asset speciJcity is compensated for by a sufficient increase in the extent of product dijfkrentiation. W George Hendrikse is 3t the Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…In a worker-owned co-operative, the economic incentive for membership is the expectancy of higher wages (including the right to the surplus according to their work activity) one can get through working in a firm owned by the workers themselves instead of an outside investor (Johnson, 2006;Bataille-Chedotel & Huntzinger, 2004). In a farmers' (marketing) co-operative, a farmer's membership in the co-operative is motivated by a higher price for inputs though supplying the co-operative as opposed to contracting with an investor-owned processor (Hendrikse & Veerman, 2001). According to Tuominen et al, (2009), members of consumer co-operatives also steer their co-operative through buying the goods and services that they consider as delivering the most value.…”
Section: Economic Exchange Interest and Expectation Of Economic Gainsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a worker-owned co-operative, the economic incentive for membership is the expectancy of higher wages (including the right to the surplus according to their work activity) one can get through working in a firm owned by the workers themselves instead of an outside investor (Johnson, 2006;Bataille-Chedotel & Huntzinger, 2004). In a farmers' (marketing) co-operative, a farmer's membership in the co-operative is motivated by a higher price for inputs though supplying the co-operative as opposed to contracting with an investor-owned processor (Hendrikse & Veerman, 2001). According to Tuominen et al, (2009), members of consumer co-operatives also steer their co-operative through buying the goods and services that they consider as delivering the most value.…”
Section: Economic Exchange Interest and Expectation Of Economic Gainsmentioning
confidence: 99%
“…For example farmers do not know the final price for their supply, but there is an explicit price that is used during a particular period (cf. Hendrikse & Veerman, 2001). Some explicit bargaining (concerning the wages) takes place in worker co-operatives too and in consumer co-operatives the members can simply look at the price tag to see what they have to pay for particular product or service.…”
Section: Forms Of Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…It is basically a loose connection of agency theory, transaction cost economics and property right-incomplete contract theory. A detailed discussion of this approach can be accessed through different authors' works (for example, Eilers and Hanf, 1999;and Hendrikse and Veerman, 2001). As with the other two categories, the theoretical framework in this subcategory is built on the neoclassical rational choice model.…”
Section: Standard Theory Of Cooperativementioning
confidence: 99%
“…They argue that the farmer cooperative economy organization can reduce the farmers' transaction costs through reducing the actual impact of these factors. For example, agricultural investment has a high asset specificity (Caves and Petersen 1986;Staatz 1987;Schaffer 1987;Hendrikse and Veerman 2001), the farmer cooperative economy organization can reduce the transaction cost caused by the asset specificity (Royer 1995); the farmer cooperative economy organization can better deal with the influences of uncertain factors in agricultural production, such as weather, market price, trading conditions and so on (Shaffer 1987;Fulton 1995); the farmer cooperative economy organization has a lower transaction frequency and a higher market developing ability than an individual farmer, so it can reduce the transaction risk and transaction costs, and ensure that the farmers get a relatively stable income (Sexton and Iskow 1988;Ollia and Nilsson 1997); the farmer cooperative economy organization can reduce the opportunistic behaviour in introduction new varieties, new technology and business training (Staaz 1984), and it also can produce the power of objection to the market monopoly (Bijman and Hendrikse 2003), to reduce the transaction cost. In addition, the studies have shown that the farmer cooperative economy organization can provide various services, including credit, etc., and reduce the transaction cost and improve the bargaining power of small farmers (Sharma 2007); the farmer cooperative economy organization can also achieve the agriculture industrialization by reducing the transaction cost and risk and establishing the trust of vertical cooperation (Hoeffler 2006).…”
mentioning
confidence: 99%